2016
DOI: 10.21608/jpp.2016.43461
|View full text |Cite
|
Sign up to set email alerts
|

ECOLOGICAL STUDIES ON WILD MEDICINAL PLANTS IN EGYPT. III- Cynanchum acutum L.

Abstract: The present work contributes information about morphology and anatomy of Cynanchum acutum. Also, it comprises a detailed ecological study on C. acutum community type. Phytochemically, the mean values of flavonoids and polyphenols were detected. The GLC analysis of fatty acids was carried out and the antioxidant and antimicrobial activities of methanolic extract were examined. In all the stands, Cynanchum was the dominant and produced the greatest part of the dense plant cover. Chenopodium murale, Cynodon dacty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Vascular system represented by large vascular bundle crescent shape in the mid rib region and small vascular bundles in the leaf lamina. The results of present stuy are in agreement with the findings of AbuZiada, et al (2016). Cross section of leaf blade of Erodium ciconium showed that epidermis is composed of uniseriate small tangentially compactly arranged cells covered with thick and smooth cuticle on both surface.…”
supporting
confidence: 92%
“…Vascular system represented by large vascular bundle crescent shape in the mid rib region and small vascular bundles in the leaf lamina. The results of present stuy are in agreement with the findings of AbuZiada, et al (2016). Cross section of leaf blade of Erodium ciconium showed that epidermis is composed of uniseriate small tangentially compactly arranged cells covered with thick and smooth cuticle on both surface.…”
supporting
confidence: 92%